Establishment of Seed Production Area of Artocarpus hirsuta in Kerala - Hegde, Maheshwar; Sekaran, S.; Sivabalakrishnan, K.; Singh K., B. G.; , Siddappa (Indian Forester, 2003)
A 10 hectare Artocarpus hirsuta plantation (1959) at Palode in Thiruvananthapuram Division in Kerala was selected for Seed Production Area (SPA) through sample plot analysis and converted into SPA after culling inferior trees. Ranking of trees was done using point grade method. To overcome soil fertility gradient in the stand blocks were made and enumeration , scoring and ranking was done separately for each block. This is the first report of establishing SPA in this species. This SPA can be used as seed source for future planting and also can be maintained as unique ex-situ conservation stand.